A Multilevel Assessment of Plasticity in Response to High-Altitude Environment for Agama Lizards - Qi, Yin; Zhang, Tao; Wu, Yayong; Yao, Zhongyi; Qiu, Xia; Pu, Peng; Tang, Xiaolong; Fu, Jinzhong; Yang, Weizhao (Frontiers in Ecology and Evolution, 2022)
Upslope range shifting has been documented in diverse species in response to global warming. Plasticity, which refers to the ability for organisms to alter their phenotypes in changing environments, is crucial for the survival of those that newly migrated to a high-altitude environment. The scope and mechanisms of plasticity across biological levels, however, have rarely been examined. We used two agama lizards (genus Phrynocephalus) as model systems and a transplant experiment to comprehensively assess their plasticity on multiple organization levels. Two low-altitude (934 m) agama species, P. axillaris (oviparous) and P. forsythii (viviparous), were transplanted to a high-altitude site (3,400 m). After acclimation for six weeks in semi-natural enclosures, plasticity was measured from bite force, tail display behavior, gene expression, and metabolome. Both lizards were capable to acclimate to the high-altitude environment without sacrificing their performance in bite force but they also showed high plasticity in tail display behavior by either decreasing the intensity of a specific display component (P. forsythii) or by trade-off between display components (P. axillaris). Genes and metabolites associated with lipids, especially fatty acid metabolism, exhibited significant differentiation in expression, compared to individuals from their native habitats. Improved fatty acid storage and metabolism appeared to be a common response among animals at high altitudes. Despite distinct reproductive modes that may differ in response to physiological pressure, the two lizards demonstrated high concordance in plasticity when they faced a novel environment at high altitude. Taken together, lizards likely acclimate to high-altitude environments by reducing behavioral activity and increasing energy efficiency after range shifting. Our results provide new insights into our understanding of phenotypic plasticity and its importance in today’s changing climate.